Insights into the H2O2‐driven catalytic mechanism of fungal lytic polysaccharide monooxygenases. (26th January 2021) - Hedison, Tobias M.; Breslmayr, Erik; Shanmugam, Muralidharan; Karnpakdee, Kwankao; Heyes, Derren J.; Green, Anthony P.; Ludwig, Roland; Scrutton, Nigel S.; Kracher, Daniel
Abstract : Fungal lytic polysaccharide monooxygenases (LPMOs) depolymerise crystalline cellulose and hemicellulose, supporting the utilisation of lignocellulosic biomass as a feedstock for biorefinery and biomanufacturing processes. Recent investigations have shown that H2 O2 is the most efficient cosubstrate for LPMOs. Understanding the reaction mechanism of LPMOs with H2 O2 is therefore of importance for their use in biotechnological settings. Here, we have employed a variety of spectroscopic and biochemical approaches to probe the reaction of the fungal LPMO9C from N. crassa using H2 O2 as a cosubstrate and xyloglucan as a polysaccharide substrate. We show that a single 'priming' electron transfer reaction from the cellobiose dehydrogenase partner protein supports up to 20 H2 O2 ‐driven catalytic cycles of a fungal LPMO. Using rapid mixing stopped‐flow spectroscopy, alongside electron paramagnetic resonance and UV‐Vis spectroscopy, we reveal how H2 O2 and xyloglucan interact with the enzyme and investigate transient species that form uncoupled pathways of Nc LPMO9C. Our study shows how the H2 O2 cosubstrate supports fungal LPMO catalysis and leaves the enzyme in the reduced Cu + state following a single enzyme turnover, thus preventing the need for external protons and electrons from reducing agents or cellobiose dehydrogenase and supporting the binding of H2 O2 for further catalytic steps. We observe that the presence of the substrate xyloglucan stabilises the Cu + state of LPMOs, which may prevent the formation of uncoupled side reactions. Abstract : Lytic polysaccharide monooxygenases (LPMOs) consume external electrons and an O2 ‐containing cosubstrate to depolymerise recalcitrant polysaccharides. We show that interactions of reduced LPMO with the H2 O2 cosubstrate leaves the enzyme in a reduced Cu + state after a single turnover. This allows for continued catalysis without the need for external electrons. The presence of substrate stabilises the Cu + state of LPMOs, which may prevent the formation of uncoupled side reactions.